2010
DOI: 10.2165/11532820-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity/Race, Use of Pharmacotherapy, Scope of Physician-Ordered Cholesterol Screening, and Provision of Diet/Nutrition or Exercise Counseling during US Office-Based Visits by Patients with Hyperlipidemia

Abstract: These findings reveal a disparity in use of pharmacotherapy for hyperlipidemia, physician-ordered/provided cholesterol screening, diet/nutrition counseling, and exercise counseling by ethnicity/race. Further research is required to discern, in greater detail, reasons for the observed differences reported, and to ensure equitable access to established standards of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 22 publications
0
21
1
Order By: Relevance
“…20 A 2005 National Ambulatory Medical Care Survey study reported less-aggressive lipid screening and management for blacks than whites. 21 This study builds on these prior observations by reporting findings by race–sex group across CHD risk categories, revealing that WM were likely driving previous findings.…”
Section: Discussionmentioning
confidence: 53%
“…20 A 2005 National Ambulatory Medical Care Survey study reported less-aggressive lipid screening and management for blacks than whites. 21 This study builds on these prior observations by reporting findings by race–sex group across CHD risk categories, revealing that WM were likely driving previous findings.…”
Section: Discussionmentioning
confidence: 53%
“…The US National Ambulatory Medical Care Survey from 2005 revealed marked inequities in assessment and management of dyslipidemia by respondents' race-ethnicity [17]. Among nearly 3,500 older primary care patients with hypertension and dyslipidemia, we use a novel approach to assessing the potency of prescribed lipid lowering therapy as a potential explanatory factor contributing to these inequities.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Latino individuals are less likely to be screened for high cholesterol than non-Hispanic whites, 3 even though they are at higher risk for the condition. 4–6 Obesity, a known risk factor for high cholesterol, 7,8 is more prevalent in the Latino population, 6,9 but obese Latinos are less likely to be counseled on weight reduction, 10,11 screened for elevated lipids, 11 and diagnosed with a lipid disorder. 12 Research in this area has largely utilized cross-sectional methods that are unable to track services over time, or has relied on surveys that are subject to recall and other biases, 1317 which have produced mixed findings.…”
Section: Introductionmentioning
confidence: 99%